Acoustic climate in the environment of the selected road sections in Poland - Błażejczyk, Krzysztof; Baranowski, Jarosław (1970– ). Autor (IGiPZ PAN, 2015)
Traffic noise is an inherent element of contemporary societies’ life. Its volume systematically increases as the car number is growing and the road network is developed. Traffic noise, especially road-induced noise, is so widespread in our environment that it is hard to isolate ourselves from it. This paper presents the results of acoustic climate studies conducted in the vicinity of selected road sections in Poland: national road DK8 in the vicinity of Budzisko and Augustów, S8 road near Wyszków and at the final stretch of DK 8 in the vicinity of Kudowa-Zdrój. The studies also covered two areas adjacent to A1 motorway in the vicinity of Kamionek and Pelplin and next to road DK 91, which runs in parallel to A1 motorway. Acoustic climate studies were also carried out along A4 motorway and national road DK 94 in the vicinity of Lewin Brzeski. Measurements were made along the Buszyce–Magnuszewice profile. Noise measurements were made on a total of 11 profiles. The analysis covered certain features of the acoustic climate (equivalent sound level, its maximum and minimum values and duration of noise of a given level). Acoustic climate features were compared with data on traffic intensity and vehicle type structure along the road sections under analysis. The paper also discusses sound propagation in the vicinity of transport routes and the impact of local environment characteristics (landscape relief and humidity) on noise propagation. Possible noise level reduction means to be applied in the vicinity of roads are also discussed.
24 cm